ANALISIS PERMINTAAN TEPUNG TERIGU OLEH PEDAGANG GORENGAN DI KOTA BANDAR LAMPUNG - Yohana Agustina Gultom; Wuryaningsih Dwi Sayekti; Eka Kasymir (Lampung University, 2017)
The objectives of this research were to know the composition of the use of various types of flour, the pattern purchase of wheat flour and factors that affected the demand of wheat flour by fried food sellers in Bandar Lampung. The research was conducted intghe city of Bandar Lampung purposely. The samples that used in this study were 60 sellers chosen by proportional random sampling method. Research data was analyzed by descriptive and inferential statistics using tendency size central and regression linear analysis. The result showed that other types of flour that used to make fried food was rice flour and sagu flour, but the use of wheat flour were more dominant than any other flour. Rice flour and sagu flour used as complements of the wheat flour. The average purchase frequency of wheat flour was 5.53 time per week, with the average amount 68.27 kg per week. Brand of wheat flour most often used was Tambang and the sellers choose the traditional market to buy the wheat flour. The factors that positively affected the demand of wheat flour were the price of cabbage, the number of buyer and the turnover. The factors that negatively added the demand of wheat flour were the price of wheat flour and the price of cooking oil. Key words: composition, demand, pattern,wheat flour